2017
DOI: 10.1145/3134704
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Foreign Language Posts in Social Media

Abstract: Many people's social media feeds include posts in languages they do not understand. While previous research has examined bilingual social media users' language choices, little research has focused on how people make sense of foreign language posts. In the present study, we interviewed 23 undergraduate social media users about how they consume and make sense of posts in other languages. Interviewees reported that they often did not pay attention to or engage with foreign language posts, due to a lack of relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The findings suggest that MT helped the Chinese participants to produce ideas in English, but both groups found the English messages that were not mediated by MT to be more comprehensible. Lim and Fussell (2017) analyse how people understand social posts in languages they do not understand. They found that users not only rely on MT to understand messages, but also on the context of the message by means of visual content (pictures and emojis), contextual and cultural cues, and background knowledge, among others.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings suggest that MT helped the Chinese participants to produce ideas in English, but both groups found the English messages that were not mediated by MT to be more comprehensible. Lim and Fussell (2017) analyse how people understand social posts in languages they do not understand. They found that users not only rely on MT to understand messages, but also on the context of the message by means of visual content (pictures and emojis), contextual and cultural cues, and background knowledge, among others.…”
Section: Related Workmentioning
confidence: 99%
“…However, target language participants did report on words that were wrong, incorrect or confusing (as per Table 1) in the MT scenario, and these terms created difficulties when completing the tasks. To overcome these difficulties, they resorted to their previous experience, checked the context, checked the visual icons, or they back-translated the term (into English), as in Lim and Fussell (2017) and Pituxcoosuvarn et al (2018).…”
Section: Language In the Word Applicationmentioning
confidence: 99%
“…Language differences pose not only the immediate barrier of understanding the other language, but the more general barrier of cultural and contextual differences [7][30] [33] because languages are often associated with specific countries or cultures. By themselves, machine translations help address the first issue but not the second, which has been found to be a key problem for people when making sense of foreign language posts in social media [24].…”
Section: Making Sense Of Foreign Language Social Media Postsmentioning
confidence: 99%
“…As it is increasingly common to encounter foreign language posts in one's feed [1][9], social media sites including Facebook, Instagram, and Twitter have incorporated machine translation (MT) features (e.g., [46]) into their interfaces to help users to understand and interact with posts in foreign languages. While the overall quality of MT continues to improve, recent studies [24] show that social media users still have trouble making sense of foreign language posts because MT quality is inconsistent, particularly given the colloquial nature of much social media content [4], [15]. Even when MT produces reasonable translations, these translations often do not help readers understand the cultural and contextual meanings around foreign language posts [24] [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation